Predictive factors for the appearance of myringosclerosis after myringotomy with ventilation tube placement: randomized study - Branco, C (2016)
Myringotomy with the insertion of ventilation tubes is the most frequent surgical procedure performed in children, and the appearance of myringosclerosis is one of its most frequent long-term complications. The objective of this study is to identify clinical factors and technique variations that may have a relation with the appearance of myringosclerosis, after tube insertion. Patients submitted to myringotomy with transtympanic short-term tube insertion were studied in a longitudinal prospective and analytical cohort study with the prospective randomized open, blinded endpoint (PROBE) methodology, to study the influence of the location of myringotomy (anterior-inferior quadrant or posterior-inferior), directions of the incision (radial or non-radial) and aspiration or not of the middle ear. Our study included 156 patients (297 ears). Myringosclerosis was observed in 35.7 % of the operated ears. It appeared more often in patients with greater number of otitis (p = .001) and with greater number of otorrhea episodes (p = .029) and in patients in whom the tympanogram after the tube extraction was type A (according to Jerger´s classification) (p = 0.016). We identified myringosclerosis in less patients, if the tube was in the tympanic membrane for less than 12 months (p = .009). Myringosclerosis was present more extensively if the tympanic incision was located in the anterior-inferior quadrant, with tympanic involvement superior to 25 % (p = .015). The results observed prove that, underlying the appearance of myringosclerosis, there exists an early inflammatory or infectious process and a final cicatricial process. It was also found that when myringotomy is made in the anterior-inferior quadrant, myringosclerosis appears in a higher percentage of the tympanic membrane; therefore, it is not recommended to do the incision in this quadrant, because it may lead to a reduction of the tympanic membrane vibration.